2010
DOI: 10.1073/pnas.1014509107
|View full text |Cite
|
Sign up to set email alerts
|

Experimental human cytomegalovirus latency in CD14+monocytes

Abstract: CD14 + monocytes are a reservoir for latent human cytomegalovirus, and virus replication is reactivated during their differentiation to macrophages or dendritic cells. It has not been clear whether the virus can establish latency upon direct infection of monocytes or whether it must first become quiescent in a progenitor cell that subsequently differentiates to generate a monocyte. We report that infection of primary human monocytes with a clinical strain of human cytomegalovirus exhibits the hallmarks of late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
206
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(217 citation statements)
references
References 45 publications
(44 reference statements)
9
206
1
1
Order By: Relevance
“…The goal of the present study is to identify additional candidates that may contribute to reactivation of IE gene expression in allogeneic transplants, with the long-term goal of developing novel therapeutic approaches to preventing reactivation of the virus. In addition to the TNF/NF-k B and IL-6/mitogen-activated protein kinase (MAPK) signalling pathways, which have been previously implicated in reactivation of HCMV (Döcke et al, 1994;Fietze et al, 1994;Hargett & Shenk, 2010;Huang et al, 2012;Kew et al, 2014;O'Connor & Murphy, 2012;Prösch et al, 1995;Reeves & Compton, 2011;Stein et al, 1993), we have identified novel signalling pathways that have not to our knowledge been previously associated with reactivation of HCMV. Our results suggest that it may be necessary to target multiple signalling pathways to prevent transcriptional reactivation of CMV.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The goal of the present study is to identify additional candidates that may contribute to reactivation of IE gene expression in allogeneic transplants, with the long-term goal of developing novel therapeutic approaches to preventing reactivation of the virus. In addition to the TNF/NF-k B and IL-6/mitogen-activated protein kinase (MAPK) signalling pathways, which have been previously implicated in reactivation of HCMV (Döcke et al, 1994;Fietze et al, 1994;Hargett & Shenk, 2010;Huang et al, 2012;Kew et al, 2014;O'Connor & Murphy, 2012;Prösch et al, 1995;Reeves & Compton, 2011;Stein et al, 1993), we have identified novel signalling pathways that have not to our knowledge been previously associated with reactivation of HCMV. Our results suggest that it may be necessary to target multiple signalling pathways to prevent transcriptional reactivation of CMV.…”
Section: Introductionmentioning
confidence: 82%
“…Allograft rejection, sepsis, acute illness, IL-6 and TNF have long been implicated in reactivation of HCMV in patients (Cook et al, 1998;Döcke et al, 1994;Fietze et al, 1994;Grattan et al, 1989;Heininger et al, 2001;Hibberd et al, 1992;Kalil & Florescu, 2009;Kutza et al, 1998;Lao et al, 1997;Limaye et al, 2008;Mutimer et al, 1997;Portela et al, 1995;Razonable et al, 2001;Reinke et al, 1994a) and allogeneic stimulation, TNF, IL-6 and lipopolysaccharide have been shown to induce reactivation of HCMV in experimental models (Hargett & Shenk, 2010;Huang et al, 2012;Kew et al, 2014;O'Connor & Murphy, 2012;Reeves & Compton, 2011;Söderberg-NauclĂ©r et al, 1997). Allogeneic transplantation and TNF are sufficient to activate both an HCMV MIEP-lacZ transgene and MCMV IE gene expression (Hummel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…CD34 1 progenitors, monocytes and granulocyte-macrophage progenitors, as well as some established myeloid cell lines, can be infected in culture allowing the maintenance of latent viral genomes which can then be reactivated by differentiation signals. 21,30,[35][36][37][45][46][47] However, it is clear that some experimental models using established cell lines do not appear to fully recapitulate all aspects of control of latency and reactivation observed in primary myeloid cells. 48 A totally quiescent viral genome during latent infection would clearly be the ideal way to avoid immune surveillance-if viral proteins are not expressed at all there would be no processing and presentation of viral antigens to specific T cells and, thus, latently infected cells would be ignored by the host immune response.…”
Section: Establishment Of Latency and The Molecular Biology Of The Lamentioning
confidence: 99%
“…28 Consistent with cells of the myeloid lineage being sites of latent infection, analyses of the viral transcription programme in these cells generally shows a suppression of viral lytic gene expression 2,29-32 but concomitant expression of known latency-associated viral genes. 31,[33][34][35][36][37] Importantly, these cells do not produce infectious virions; an essential characteristic of latent infection. In latent myeloid cells in vivo, this suppression of the lytic transcription programme appears to involve repression of the viral major immediate early promoter (MIEP), which would normally drive lytic cycle, through post-translational modification of histones around the MIEP resulting in the presence of well characterized repressive chromatin marks (reviewed in Ref.…”
Section: Establishment Of Latency and The Molecular Biology Of The Lamentioning
confidence: 99%
See 1 more Smart Citation